16th Conference on Data Analysis Methods for Software Systems - Bernatavičienė, Jolita (Vilnius University Proceedings, 2025)
The 16th International Conference on Data Analysis Methods for Software Systems (DAMSS-2025) is taking place in Druskininkai, Lithuania. As in previous years, it is organized at the same venue and time, fostering active scientific exchange among participants.First organized in 2009 with 16 papers, the event began as a workshop under an international project and has evolved into a prominent conference. Founded by the Institute of Mathematics and Informatics, now the Institute of Data Science and Digital Technologies at Vilnius University, and supported by the Lithuanian Academy of Sciences and the Lithuanian Computer Society, the conference maintains high academic and organizational standards through long-term collaboration. The conference has grown into one of Lithuania’s leading events in computer science and computer engineering, promoting interdisciplinary research and fostering genuine innovation.This year, the conference features 90 presentations representing nine countries, with a total of 132 registered participants from Armenia, France, Italy, Lithuania, Poland, Romania, Slovenia, Spain, and Sweden. With participation from seven Lithuanian universities, science and higher education institutions, the conference serves as the main annual meeting for the country’s computer science community. The conference’s international character fosters project collaboration, facilitates the exchange of knowledge, and supports the development of innovative ideas on a global scale.The annual organization of DAMSS facilitates the rapid exchange of new ideas within the scientific community and is unique in providing opportunities for practical collaboration. Researchers from Lithuania and abroad, along with representatives from the industry and public sectors, are encouraged to develop joint projects, apply research to practical applications, and address both business and societal challenges, thereby aligning research with market needs and industry competencies.A key highlight of the conference is the participation of young scientists. Doctoral and Master’s students from Lithuania and other countries can present their research, engage in discussions, and gain valuable experience. This year, we have a special student presentation session. Traditionally, most presentations are delivered in poster format, providing an interactive platform for discussion and feedback. Oral sessions are mainly for keynote speakers. This year, we are pleased to invite six keynote speakers.Five IT companies and the Research Council of Lithuania support DAMSS-2025. This also demonstrates the relevance of the conference topics to the business sector.Topics covered by the conference include applied mathematics, artificial intelligence, big data, bioinformatics, blockchain technologies, business rules management, cybersecurity, data science, deep learning, high-performance computing, data visualization, machine learning, medical informatics, modelling educational data, ontological engineering, optimization, quantum computing, signal and image processing.This book compiles the presentations delivered at the DAMSS-2025 conference.